The hill station : an unfinished novel, and an Indian diary - Farrell, J. G. (James Gordon), 1935- (Weidenfeld and Nicolson, 1981)
To the cool of the Simla hills comes a reluctant Dr McNab, with his wife and young niece. For Emily, romance is in the air. For the mysterious Mrs Forester, there is scandal brewing. And for the Bishop of Simla, rainclouds are not the only storms on the horizon…[By Publisher].